Association of Fluid Management With Mortality of Sepsis Patients With Congestive Heart Failure: A Retrospective Cohort Study - Dong, Ning; Gao, Nan; Hu, Wenxin; Mu, Yuhang; Pang, Li (Frontiers in Medicine, 2022)
Sepsis management includes intravenous fluid (IVF) resuscitation, but patients with pre-existing congestive heart failure (CHF) have a higher risk of fluid overload. Further, patients with sepsis with concomitant CHF present worse clinical outcomes. Nevertheless, there is limited evidence of the association between fluid management and the outcomes of patients with concomitant sepsis and CHF. This retrospective cohort study aimed to evaluate the association between fluid management and in-hospital mortality in patients with sepsis and concomitant heart failure (HF). The patients’ data were extracted from the Multi-parameter Intelligent Monitoring in Intensive Care III Database. The primary outcome was in-hospital mortality. A restricted cubic spline model was used to explore the relationship between variables and in-hospital mortality. Logistic models were built using the linear spline function and design variables to investigate the association of fluid balance (FB), fluid intake (FI), and fluid accumulation index (FAI, calculated as the FB/FI ratio) with mortality. Overall, 1801 patients were included. The overall mortality rate was 27.7%. After adjusting for confounding variables, FAI was found to be associated with in-hospital mortality, whereas FB and FI were not. With FAI values of 0–0.42 set as references, FAI values <0 were not associated with in-hospital mortality (odds ratio [OR]: 1.078; 95% confidence interval [CI]: 0.774–1.503), whereas FAI values >0.42 were significantly associated with higher in-hospital mortality (OR: 1.461; 95% CI: 1.099–1.954). High FAI values (>0.42) were associated with high in-hospital mortality in patients with sepsis with HF, while FB and FI were not. Proper fluid management may improve the outcomes of patients with sepsis and concomitant HF.